Metacognitive beliefs and experiences : beliefs, predictions, monitoring and evaluations in well-defined and insight problem solving : thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, New Zealand - Palmer, Shane (Massey University, 2002)
The present study attempted to replicate and extend understandings of differences in the metacognitive experiences of solving insight and well-defined problems. Insight often occurs with a sudden 'Aha!' reaction compared to the more continuous progress typical for well-defined problems. Thirty-two adults completed a within-subjects computer-based problem solving task involving sets of 8 insight and well-defined problems, while providing predictions, feeling-of-warmth monitoring, and evaluations of performance. A sub-sample completed a Problem Solving Inventory (PSI) to compare global and context-specific beliefs of ability. Predictions overestimated performance in both sets, but more so for insight than for well-defined problems. However, correlations between prediction and performance were not significant for either set. No consistent difference in monitoring was found; incremental patterns dominated insight and well-defined problems equally. Averaged evaluations mirrored the overestimation effects of the predictions, although distributions of confidence accuracy were similar across sets. However, interesting correlations were found between global PSI scores and the specific measures, for both problem types. Methodological differences between the present and earlier studies may account for the lack of problem set effects. Conceptual issues need to be addressed regarding definition of insight and verification of insight experiences, particularly if future research is to reconcile metacognitive and cognitive aspects of problem solving.
Keywords: Problem solving